The Empowerment of The Joho Village Farmers Groups Through Corn Grit Production - Siswanti Siswanti; Baskara Katri Anandito; Rofandi Hartanto; Dyah Widowati (PRIMA: Journal of Community Empowering and Services, 2023)
Most of the Joho Village people depend on rice as a staple, which triggers limited economic growth in the agricultural sector. The area has abundant corn yields and is potentially processed as corn grits (rice alternative). Corn processing has solely in dry-shelled corn form, a drop in corn-shelled prices, the stagnant of the Farmers Groups Association (FGA) activity, and the lack of knowledge (food products processing, entrepreneurship, and digital marketing) underlie these community service activities. The service activities aim to optimize the program for implementing science, technology, and FGA empowerment in Joho Village to discover corn grit production potential and ensure the sustainability of FGA community activities. Therefore, the service team agreed with Joho Village FGA to organize programs: (1) Corn grit and production methods socialization (Zoom meetings and direct discussion); (2) Production equipment introduction (direct discussion); (3) Corn grits production training (hands-on practice method); (4) Entrepreneurship and digital marketing socialization (direct discussion). The questionnaire was selected as a socialization evaluation method. Joho Village FGA has high enthusiasm for activity participation (90% of attendance). The service activities succeeded in increasing corn grit production expertise (86% of yield) and improved the knowledge of corn grits (80% of increased knowledge), entrepreneurship (81.25% of increased knowledge), and digital marketing (70% of increased knowledge) of Joho Village FGA. These achievements indicated corn grit production potential as the forecast of their business opportunities in the future and embarked on the beginning of Joho Village FGA’s empowerment sustainability.